Pengelolaan Kurikulum Adadtaif Matematika pada Program Sekolah Cluster - Wulandari, Widya Syafitri; Sumardi, Sumardi (Jurnal VARIDIKA, 2015)
The aim of research to determine the planning, implementation, and evaluation of school mathematics curriculum adaptive cluster. Qualitative research with ethnographic design. Where research SMK N 2 Purwodadi. The research subject Principals, teachers, and students. Data collection techniques of interview, observation, documentation. The validity of the triangulation of data sources, techniques, time. Data analysis techniques with methods groove. The results of the study (1) Management of adaptive curriculum in math lesson planning includes designing syllabi and lesson plans that already contains a character education is the KI and KD, as well as the student's character assessment sheets .; (2) The study of mathematics includes three activities, namely the preliminary activities of teachers manage the religious character of prayer, discipline go to class on time, invite students to maintain the cleanliness of the classroom, and teachers to motivate students. Core activities, teachers implement instructional methods discussion so familiarize students have a democratic character, tolerance, social care, communicative, curiosity, love of peace, hard work, and creative. The activities cover teachers familiarize students have the responsibility and creative character by giving the task .; (3) Management of adaptive curriculum in the evaluation of mathematics learning are teachers carry out daily tests or individual assignments so students can familiarize themselves has an honest character, discipline, hard work and responsibilities. Assessment can also be done with the observation in the learning process fatherly knowing the attitude, knowledge and skills of students.